2022
DOI: 10.3390/vetsci10010020
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Antibody Responses in Beef Calves Vaccinated with a Modified-Live Virus Bovine Respiratory Syncytial Virus (BRSV) Vaccine at Birth following BRSV Infection

Abstract: Maternal antibodies interfere with BRSV vaccine responses and efficacy in young calves. The objective of this study was to determine if vaccination before the complete absorption of colostral antibodies results in adequate immune priming and clinical protection of beef calves. Within 6 h of life, calves were randomly assigned to 2 different treatment groups. Group Vacc (n = 25) received a single dose of a modified-live virus (MLV) BRSV vaccine intranasally (IN) and group Control (n = 25) received 2 mL of 0.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This recommendation contrasts with the findings of Woolums et al (2004), who previously demonstrated the efficacy of intranasal BRSV vaccination in calves, even in those with maternal antibodies. Immunohistochemical analysis conducted by Martínez et al (2023) revealed alterations in T and B cell distribution, with a notable emphasis on lung-associated lymphoid tissues and tonsils, underscoring the importance of local immune responses in their study.…”
Section: Althoughmentioning
confidence: 97%
See 1 more Smart Citation
“…This recommendation contrasts with the findings of Woolums et al (2004), who previously demonstrated the efficacy of intranasal BRSV vaccination in calves, even in those with maternal antibodies. Immunohistochemical analysis conducted by Martínez et al (2023) revealed alterations in T and B cell distribution, with a notable emphasis on lung-associated lymphoid tissues and tonsils, underscoring the importance of local immune responses in their study.…”
Section: Althoughmentioning
confidence: 97%
“…Due to these considerations, Chamorro and Palomares (2020) do not advocate for the administration of this vaccine in debilitated or stressed animals. Similarly, Martínez et al (2023) propose intranasal BRSV vaccination in calves after one month of age to mitigate interference from maternal immunity and to elicit durable local and systemic immune responses. This recommendation contrasts with the findings of Woolums et al (2004), who previously demonstrated the efficacy of intranasal BRSV vaccination in calves, even in those with maternal antibodies.…”
Section: Althoughmentioning
confidence: 99%
“…This is a particular concern for MLVs that could be inhibited by pre-existing immune responses. With respect to young animals, it is the potential for maternal antibodies to interfere with the adaptive immune responses to MLV vaccination [ 77 ]. As the maternal antibodies decline, a potential window of pathogen susceptibility can occur before the vaccines can stimulate adaptive responses.…”
Section: Immune Responses To Mrna Vaccinationmentioning
confidence: 99%
“…Some intranasal vaccines suffer from interference with maternally derived antibodies (MDA). Martinez et al, showed that modified-live virus (MLV) BRSV vaccines reduced the risk of morbidity in calves with absence of MDA at initial vaccination, but failed to demonstrate significant morbidity reduction when calves were vaccinated in the face of MDA (15).…”
Section: Barriers To Intranasal Vaccinationmentioning
confidence: 99%
“…In addition, the spaceoccupying effect also reduces the risk of population by other pathogens. This is also of benefit in an outbreak situation, allowing a more rapid immune response without the same demands on the immune system as systemic vaccination (15). Aligned with this benefit, intranasal vaccination can also be used alongside treatments if required, due to the lack of interference with the systemic immune response.…”
Section: Opportunities To Overcome Barriers To Intranasal Vaccinationmentioning
confidence: 99%